Extraction of Carboxylic Acids from Anaerobic Fermentation Processes by the Anion Exchange Resin Amberlite IRA-400(Cl) - Issa Samb; Mohamed Lamine Gaye (Earthline Journal of Chemical Sciences, 2023)
This work describes a methodology for the valorization of non-food biomass for the production of biosourced molecules via the production of biohydrogen and metabolites of fermentations such as volatile fatty acids. The commercial anion exchange resin Amberlite IRA-400(Cl) was chosen for the extraction of carboxylic acids. Different operating conditions were set up namely the amount of resin to be used, activation methods, pH and their effects on the extraction capacity of the solvent.